New Zealand Journal of Marine & Freshwater Research - New Zealand Journal of Marine & Freshwater Research (Taylor & Francis, 2026)
Aim: The New Zealand Journal of Marine and Freshwater Research is an international journal dedicated to advancing knowledge of aquatic systems, with a focus on marine, estuarine, and freshwater systems of the Southern Hemisphere. The journal serves as a key platform for disseminating high-quality observational, experimental, theoretical, and numerical research that enhances our understanding of aquatic ecosystems and processes.
FI 0.47
Q3
Keywords: Biological; Earth & Environmental Food Science; Limnología; Aguas dulces; Acuerdos transformativos; Transformative agreements; Sistemas marinos; Estuarinos; Sistemas de agua dulce; Hemisferio sur